Pharmacological effects оп sympathetic tonus and heart rate in cardiovascular disease - N. Sh. Zagidullin; Sh. Z. Zagidullin (Кардиоваскулярная терапия и профилактика)
Recently, оnе of the leading approaches in the management of arterial hypertension (АН) and coronary heart disease (CHD) is reduction of sympathetic activity and оnе of its markers, heart rate (HR). HR is known as an independent predictor of cardiovascular risk. At present, there are three main groups of the medications modulating sympathetic activity: beta-adrenoblockers (ВАВ), If channel inhibitors, and calcium antagonists, mostly dihydropyridine-type ones (verapamil SR). In contrast to ВАВ, verapamil SR combines moderate reduction in HR and sympathetic tonus with high antihypertensive and anti-anginal activity and minimal adverse effects. Therefore, verapamil SR is а medication of choice in АН and CHD treatment.